Arsenic Species in Edible Seaweeds Using In Vitro Biomimetic Digestion Determined by High-Performance Liquid Chromatography Inductively Coupled Plasma Mass Spectrometry - Yan-Fang Zhao; Ji-Fa Wu; De-Rong Shang; Jin-Song Ning; Hai-Yan Ding; Yu-Xiu Zhai (International Journal of Food Science)
Arsenite [As (III)], arsenate [As (V)], methylarsonate (MMA), and dimethylarsinate (DMA) in five edible seaweeds (the brown algae Laminaria japonica, red algae Porphyra yezoensis, brown algae Undaria pinnatifida, brown algae Hizikia fusiformis, and green algae Enteromorpha prolifera) were analyzed using in vitro digestion method determined by high-performance liquid chromatography inductively coupled plasma mass spectrometry. The results showed that DMA was found in the water extracts of all samples; As (III) were detected in L. japonica and U. pinnatifida and about 23.0 and 0.15 mg/kg of As (V) were found in H. fusiformis and E. prolifera respectively. However, after the gastrointestinal digestion, As (V) was not detected in any of the five seaweeds. About 0.19 and 1.47 mg/kg of As (III) was detected in the gastric extracts of L. japonica and H. fusiformis, respectively, and about 0.31 and 0.10 mg/kg of As (III) were extracted from the intestinal extracts of Porphyra yezoensis and U. pinnatifida, respectively. The present results successfully reveal the differences of As species and levels in the water and biomimetic extracts of five edible seaweeds. The risk assessment of the inorganic arsenic in the five edible seaweeds based on present data showed almost no hazards to human health.